A Fusion Method to Develop an Expanded Artificial Genomic RNA Replicable by Qβ Replicase. (5th August 2019) - Ueda, Kensuke; Mizuuchi, Ryo; Matsuda, Fumio; Ichihashi, Norikazu
Abstract: RNA‐based genomes are used to synthesize artificial cells that harbor genome replication systems. Previously, continuous replication of an artificial genomic RNA that encoded an RNA replicase was demonstrated. The next important challenge is to expand such genomes by increasing the number of encoded genes. However, technical difficulties are encountered during such expansions because the introduction of new genes disrupts the secondary structure of RNA and makes RNA nonreplicable through replicase. Herein, a fusion method that enables the construction of a longer RNA from two replicable RNAs, while retaining replication capability, is proposed. Two replicable RNAs that encode different genes at various positions are fused, and a new parameter, the unreplicable index, which negatively correlates with the replication ability of the fused RNAs better than that of the previous parameter, is determined. The unreplicable index represents the expected value of the number of G or C nucleotides that are unpaired in both the template and complementary strands. It is also observed that some of the constructed fused RNAs replicate efficiently by using the internally translated replicase. The method proposed herein could contribute to the development of an expanded RNA genome that can be used for the purpose of artificial cell synthesis. Abstract : Length and functionality : A replication system for RNA‐based genetic information consists of artificial genomic RNA (Beta‐RNA) that encodes a part of RNA replicase. In this study, expanded long genomic RNAs which are also replicable, are obtained by fusing two replicable RNAs.